2022
DOI: 10.1002/jssc.202200145
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of anthocyanins, flavonoids, and phenolic acids in flowers ofRhododendron arboreumand evaluation of their antioxidant potential

Abstract: The current study aimed to investigate the anthocyanins, non‐anthocyanins (flavonoids and phenolic acids), and free radicals scavenging potential in the flowers of Rhododendron arboreum using ultra high performance liquid chromatography with ion mobility quadrupole time of flight tandem mass spectrometry. A total of 25 constituents including nine anthocyanins, six phenolic acids, and ten flavonoids were identified in the flower extract. The major anthocyanins identified were cyanidin‐3‐O‐β‐galactoside (1), cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Previously, Bhatt et al, 2022, reported the presence of different phenolic acids, flavonoids, and anthocyanins in the acidified methanolic extract of R. arboreum petals by using HPLC. Various proanthocyanidins, glycosides, and hydroxycinnamates were detected from the methanolic extracts of leaves from 14 Rhododendron species using LC-MS (Jaiswal et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, Bhatt et al, 2022, reported the presence of different phenolic acids, flavonoids, and anthocyanins in the acidified methanolic extract of R. arboreum petals by using HPLC. Various proanthocyanidins, glycosides, and hydroxycinnamates were detected from the methanolic extracts of leaves from 14 Rhododendron species using LC-MS (Jaiswal et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…R. arboreum has red-colored petals and are consumed by local inhabitants in various forms, such as juices, jams, pickles, and chutney (Gautam et al, 2020; Kumar et al, 2019). Traditionally, these red petals in various forms (fresh, dried, and juice) are used for the treatment of various ailments like diarrhea, blood dysentery, high altitude sickness, headaches, diabetes, rheumatism, etc (Bhatt et al, 2022; Lingwan et al, 2021). The young leaves of R. arboreum have medicinal properties and are applied on the forehead to relieve headaches but cause intoxication in large quantities (Watt, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPC and TFC were estimated according to the method reported earlier from our laboratory with some modifications [23][24][25].…”
Section: Estimation Of Tpc and Tfcmentioning
confidence: 99%
“…Estimation of Total Anthocyanin Content. Total anthocyanin content (TAC) was estimated using the method described by Bhatt et al 75 The flower samples were extracted in acidified methanol (0.1 M HCl; 10 mL) under sonication at 35 °C for 30 min. The TAC was quantified using the pH differential method.…”
Section: Proximate and Nutrient Analysis Of Edible Flowersmentioning
confidence: 99%